Dense water formation in the north‐western Mediterranean area during HyMeX‐SOP2 in 1/36° ocean simulations: Ocean‐atmosphere coupling impact. Issue 7 (17th July 2017) - Lebeaupin Brossier, Cindy; Léger, Fabien; Giordani, Hervé; Beuvier, Jonathan; Bouin, Marie‐Noëlle; Ducrocq, Véronique; Fourrié, Nadia
Abstract: The north‐western Mediterranean Sea is a key location for the thermohaline circulation of the basin. The area is characterized by intense air‐sea exchanges favored by the succession of strong northerly and north‐westerly wind situations (mistral and tramontane) in autumn and winter. Such meteorological conditions lead to significant evaporation and ocean heat loss that are well known as the main triggering factor for the Dense Water Formation (DWF) and winter deep convection episodes. During the HyMeX second field campaign (SOP2, 1 February to 15 March 2013), several platforms were deployed in the area in order to document the DWF and the ocean deep convection, as the air‐sea interface conditions. This study investigates the role of the ocean‐atmosphere coupling on DWF during winter 2012–2013. The coupled system, based on the NEMO‐WMED36 ocean model (1/36° resolution) and the AROME‐WMED atmospheric model (2.5 km resolution), was run during 2 months covering the SOP2 and is compared to an ocean‐only simulation forced by AROME‐WMED real‐time forecasts and to observations collected in the north‐western Mediterranean area during the HyMeX SOP2. The comparison shows small differences in terms of net heat, water, and momentum fluxes. On average, DWF is slightly sensitive to air‐sea coupling. However, fine‐scale ocean processes, such as shelf DWF and export or eddies and fronts at the rim of the convective patch, are significantly modified. The wind‐current interactions constitute an efficient coupled process at fine scale, acting as a turbulence propagating vectors, producing large mixing and convection at the rim of the convective patch. Key Points: The AROME‐NEMO WMED coupled model was run over HyMeX SOP2 and compared to a uncoupled ocean simulation validated against observations Air‐sea coupling induces small differences in surface fluxes and in dense water formation (chronology, characteristics, and volumes) Fine‐scale ocean structures around and interacting with the convective patch are the most sensitive to the air‐sea coupling